Assessment of the soil erosion and sedimentation levels of selected Small Water Impounding Systems (SWIS) in Nueva Ecija, Philippines - Camania, Denver C.; Malamug, Vitaliana U.; Castillo, Claire Marie M.; Fabula, Jonathan V.; Sacdalan, John Paulo C.; Badua, Sylvester A.; Reños, Erwin B.; Samson, Richard V.; Almerol, Carolyn Grace S. (Journal of Degraded and Mining Lands Management, 2026)
The Philippines was able to implement around 740 small water impounding systems (SWIS) from 1974-2021, which reportedly irrigated a service area of more than 27,000 hectares, benefiting about 26,600 farmers. Unfortunately, these projects are facing an alarming sedimentation problem due to soil erosion at upstream watersheds. It was observed that limited studies have been undertaken for the past 10 years that investigate the status of SWIS, especially the governing relationship between soil erosion and reservoir sedimentation. The present study was driven by these problems to provide a picture of its current levels of severity and its effects on the project itself. The six (6) selected sites were situated in the north-western portion of Nueva Ecija province, namely Villa Isla, Mangandingay, Villa Boado, Maasin, Tibag II, and Alalay Grande SWIS. The soil erosion component of the study was evaluated using the Modified Universal Soil Loss Equation (MUSLE) and Quantum Geographic Information System (QGIS). While the sediments deposited at the SWIS reservoir were measured using the Real-Time Kinematic (RTK) equipment. It was found out that these sites were now experiencing soil erosion from slight to moderate, 3.21 t/ha/year, to extremely high, 100.35 t/ha/year. In effect, the level of sedimentation within the reservoirs reached the intensity from slight to high with values ranging from 2.20-26.11 t/ha/year. Thus, recording an average reservoir storage loss of 702.86 m3/year or 2.86%/year which equated to average remaining useful life of 37.01 years, at 100% capacity of the reservoir.